Analisis Pola Minat Siswa Lulusan SMU/SMK Untuk Melanjutkan Kuliah dengan Menggunakan Algoritma C4.5 - Ayunda, Yuli Septya; Hartama, Dedy; Lubis, Muhammad Ridwan; Gunawan, Indra; Rafai, Muhammad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
STIKOM Tunas Bangsa is one of the best private universities in the city of Pematangsiantar. With so many universities in the city of Pematangsiantar, it certainly creates competition in attracting prospective new students. In order to maintain the number of students each year, universities must know what factors are the main drivers for prospective students to continue their studies at STIKOM Tunas Bangsa. The aim of this research is to determine the main factors for high school/vocational school graduate students in continuing their studies at STIKOM Tunas Bangsa. Data was obtained from questionnaires which were then processed using data mining with the C4.5 algorithm and tested with Rapid Miner software. Based on the research results, it can be concluded that there are six (6) patterns produced in cases of interest in prospective students who will study at STIKOM Tunas Bangsa, where three (3) of these rules result in interest decisions and three (3) rules result in no interest decisions. One of the resulting rules is if Recommendation = Never, and Suitability of Department = Appropriate, then the result is Interest. Recommendations from local people are the main supporting factor for high school/vocational school graduate students to continue studying at STIKOM Tunas Bangsa Pematangsiantar.